Kontribusi persepsi kompetensi manajerial kepala sekolah, motivasi berprestasi, dan lingkungan kerja terhadap kinerja guru SMP Negeri se-Kecamatan Sapuran, Wonosobo - Setyowibowo, Bambang; Jaenullah, Jaenullah (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose – This paper examined contribution of principal managerial competence perception, achievement motivation, and working environment simultaneously to the work performance of the teachers of State Junior High School os sub district 3 in Sapuran Wonosobo both simultaneously and partially. Method − This research was a quantitative research. The population of the research were all the Goverment servant teachers as much as 279 people with samples were 124 people. The data were taken by using questionare. The analysis was done by using multiple linear regression by simultaneous and partial technique Findings − The result showed that ; (1) There is a positive and significance contribution simultaneously between the principal managerial competence perception, achievement motivation, and working environment to the work teachers performance of Junior High School. (2) There is positive and significance contribution to the work performance of the teachers of junior high school.; (3) There is a positive and significance contribution of the achievement motivation to the work performance of the teachers of Junior High School.; (4) There is a positive and significance contribution of the working environment to the work performance of the teachers of Junior Hing School.